2002
DOI: 10.1002/hbm.10065
|View full text |Cite
|
Sign up to set email alerts
|

Cortical and subcortical networks underlying syncopated and synchronized coordination revealed using fMRI

Abstract: Inherent differences in difficulty between on the beat (synchronization) and off the beat (syncopation) coordination modes are well known. Synchronization is typically quite easy and, once begun, may be carried out with little apparent attention demand. Syncopation tends to be difficult, even though it has been described as a simple, phase-shifted version of a synchronized pattern. We hypothesize that syncopation, unlike synchronization, is organized on a cycle-by-cycle basis, thereby imposing much greater pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
85
1
8

Year Published

2003
2003
2014
2014

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 122 publications
(105 citation statements)
references
References 83 publications
(122 reference statements)
8
85
1
8
Order By: Relevance
“…This can be viewed as a shift from controlled to automatic timing processes. A similar shift in brain activation from cognitive to motor-related areas is also observed when subjects switch from a syncopation mode to a synchronization mode when responding to an isochronous series of external stimuli [20,[27][28][29]. Syncopated movements are thought to be performed as a series of independent movements that are planned and executed on each perception-action cycle.…”
Section: Reorganization Of Externally Guided Rhythmmentioning
confidence: 67%
“…This can be viewed as a shift from controlled to automatic timing processes. A similar shift in brain activation from cognitive to motor-related areas is also observed when subjects switch from a syncopation mode to a synchronization mode when responding to an isochronous series of external stimuli [20,[27][28][29]. Syncopated movements are thought to be performed as a series of independent movements that are planned and executed on each perception-action cycle.…”
Section: Reorganization Of Externally Guided Rhythmmentioning
confidence: 67%
“…BOLD patterns observed during continuation depend directly on whether subjects synchronize (move coincident with stimuli) or syncopate (move between stimuli) with the pacing metronome (Jantzen et al, 2004) during the pacing phase. Task related differences in BOLD activity distinguishing these coordination patterns Mayville, Jantzen, Fuchs, Steinberg, & Kelso, 2002) persist during continuation despite similar sensorimotor and timing constraints. Such findings suggest that the neural representation of a temporal interval may be flexibly determined by the sensory and motor systems engaged during timing acquisition (pacing) and that subsequent temporal processing based on this interval (continuation) continues to rely on the same neural representation.…”
Section: Introductionmentioning
confidence: 99%
“…Baraldi et al (1999) found support for the participation of two separate neural populations in each hemisphere, one in M1 and one in PM1: the first being activated during contralateral finger movements only, whereas the second exhibited signal changes during movements of either hand, indicating that unimanual movements are accompanied by cortical activity in both hemispheres. Compared to paced movements, self-paced rhythmic finger movements generally recruit more and larger neuronal populations that typically include (bilateral) SMA (Halsband et al 1993;Freund 1996;Kaiser et al 2000; and (ipsilateral) PM1 (Stippich et al 2000), especially during difficult tasks (Mayville et al 2002). In addition, several research groups found unilateral cortical activation during discrete and (symmetrical) bihemispheric activation during sequential unimanual motor behaviors (Cheyne and Weinberg 1989;Pulvermüller et al 1995;Manganotti et al 1998;Andrew and Pfurtscheller 1999;Babiloni et al 1999;Pfurtscheller et al 2000), indicating the presence of an active (time-varying) cross-talk between bilateral and mesial central and prefrontal regions.…”
Section: Introductionmentioning
confidence: 99%